An Analysis of the Meaning of Slander from the Perspective of Tafsir al-Qurtubi - Roswati, Ai; Nidhom, Khoirun; Ghifari, Muhammad (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2025)
The word “fitnah” in the Qur'an has diverse and contextual meanings, so it requires in-depth exploration to understand its dimensions and implications. Through text analysis method and hermeneutic approach, this study explores Al-Qurtubi's interpretation of the verses containing the word “fitnah”. The word “fitnah” in the Qur'an has a broad and diverse meaning, depending on the context of the verse. According to Imam Al-Qurtubi in his tafsir book, “Al-Jami' li Ahkam Al-Qur'an”, the word “fitnah” and its derivatives are mentioned in various forms, including verbs (fi'il), nouns (isim), and adjectives. “fitnah” and its derivatives are mentioned around 60 times in the Qur'an. However, this number may vary depending on the way the word is counted and interpreted. The word fitnah in its base form (isim) is mentioned 34 times in the Quran and in its verb (fi'il) and adjective forms is mentioned 26 times in the Quran. The results showed that Al-Qurtubi interpreted fitnah in various contexts, such as tests, trials, chaos, misguidance, and torment. This study also reveals the importance of historical, linguistic, and social contexts in Al-Qurtubi's interpretation, as well as the relevance of the concept of fitnah in contemporary life. Kata